2018
DOI: 10.24237/djps.1401.345c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Congo Red on Nano MgO Particles Prepared by Molten Salt Method

Abstract: Nano-substances show many surface properties due to their high activity and high surface area. This study concentrates on the possibility of using nano-MgO (NMO) for removing Congo red (CR) dye from wastewater. The effects of equilibrium time, pH, dye concentration and temperature have been investigated. Isotherm studies revealed the favorability of the adsorption process and the energy of adsorption (10.38 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…which they can be constituted in a cubic phase of MgO according to JPCDS card no. 45-0946 at 2θ = 37.02°, 43.02°, 58.72°, 76.78°, and 78.73° correspond to the plane (111), ( 200), ( 220), ( 311) and (222) [24,25]. No additional peaks were present in the XRD pattern indicated that the sample is highly pure, with no detectable impurities or additional phases.…”
Section: Temporal Testmentioning
confidence: 92%
See 1 more Smart Citation
“…which they can be constituted in a cubic phase of MgO according to JPCDS card no. 45-0946 at 2θ = 37.02°, 43.02°, 58.72°, 76.78°, and 78.73° correspond to the plane (111), ( 200), ( 220), ( 311) and (222) [24,25]. No additional peaks were present in the XRD pattern indicated that the sample is highly pure, with no detectable impurities or additional phases.…”
Section: Temporal Testmentioning
confidence: 92%
“…The FESEM images captured with this instrument were utilized to examine the morphology, assess agglomeration, and measure the particle size of the MgO nanoparticles in the magnification of 25kX and 100kX. Meanwhile, the XRD analysis conducted on PANalytical XPert PRO operating at Cu K radiation (λ = 1.5406 Å) in the 2θ range of 10-80 degrees, with a scanning step of 0.05 degrees and a scan speed of 5 degrees per minute as referred to Bdewi et al, [24]. XRD analysis was utilized to validate the purchased MgO nanoparticles, assess their purity, and determine particle size by identifying crystal structures and analyzing diffraction peaks.…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%